Portofolio as Self-Reflection as Assesment Tool in Clinical Education - Anindita, Pritartha S.; Rawis, Joulanda A.M; Munayang, Herdy; Jim, Edmond L.; Lantang, Eka Y. (Syntax Corporation, 2024)
Clinical education is an important part of medical education. Clinical education aims to equip medical students with the clinical skills and knowledge necessary to become competent doctors. The purpose of this study was to examine the role of portfolios as self-reflection as an assessment tool in clinical education. This research used a qualitative approach with a case study method. The data collection technique in this study was a literature study. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation and conclusion drawing. The results showed that portfolios can be used as an effective self-reflection and assessment tool in clinical education. Portfolios can help medical students to learn more effectively, to improve the link between theory and practice, and to improve communication and cooperation between students.